Molecular reorientation in a dehydration process of an organic polar salt of 2, 4-diaminotoluene/L(+)-tartaric acid. Issue 1 (23rd February 2017) - Ju, Weicai; Qiu, Simin; Tao, Yaqiu; Shen, Xiaodong; Pan, Zhigang
Abstract : An organic polar hydrate was obtained through cocrystallization of 2, 4-diaminotoluene (2, 4-DAT) and L(+)-tartaric acid (TA) from ethanol. Dehydration behavior of the obtained hydrate was investigated using variable temperature powder X-ray diffraction (PXRD) and thermal analysis. Proton transfer from L(+)-TA to 2, 4-DAT in both hydrate and dehydrated form was revealed via Fourier transform infrared spectroscopy. The crystal structures of both forms were determined using PXRD techniques. The similarities and differences between two crystal structures were analyzed and the role of water in the hydrate crystal structure was demonstrated.